The application of RFID system in water level monitoring - Mahdin, Hairulnizam; Kamaludin, Hazalila; Saedudin, RD Rohmat; Omar, Abdul Halim; Kasim, Shahreen; Jailani, Junaidah (Insight - Indonesian Society for Knowledge and Human Development, 2017)
In a tropical country like Malaysia water tank is very common in every buildings and houses. Water from the tank will be used when there is a problem with the direct water supply. It is so important where at some government buildings the water level in the tank is being inspected daily to ensure the water level is above the required threshold. However, this task consumes time and energy as the tank is located at the top of the building that cannot be easily accessible. Therefore, there is need to implement an automatic system that can monitor the level of the water in the tank. If the level is decreasing below the required threshold, the intended personnel will be informed immediately via a smartphone for example. The decrease could indicate a failure in the mechanical system to pump the water into the tank. Results from the experiments show that Radio Frequency Identification (RFID) technology has the potential to be used in monitoring the tank water level although there is drawback such implementation cost due to hardware requirements.